Comparative investigation on macroscopic and microscopic characteristics of impingement spray of gasoline and ethanol from a GDI injector under injection pressure up to 50 MPa - Xiang Li; Dayou Li; Pavlos Dimitriou; Tahmina Ajmal; Abdel Aitouche; Raouf Mobasheri; Oyuna Rybdylova; Yiqiang Pei; Zhijun Peng (Energy Reports, 2023)
Particulate Matter (PM) emissions from passenger vehicles have attracted considerable interest over the last decade. In order to reduce PM emissions, improving maximum injection pressure has been a developing trend for new generation GDI engines. However, comparing gasoline and ethanol impingement spray characteristics from a GDI injector under high injection pressure is still unclear. In this paper, a comparative investigation on both the macroscopic and microscopic characteristics of impingement spray from a GDI injector fuelled with gasoline and ethanol was performed under injection pressure up to 50 MPa, providing new findings to promote a more homogeneous air–fuel mixture and reduce PM emissions. The experimental results show that under the same PI(injection pressure), rebound height of gasoline impingement spray is a bit higher than ethanol. AS(spray area) of gasoline is slightly higher than ethanol under PI=10MPa. However, under PI=30MPaand PI=50MPa, ASof gasoline is gradually exceeded by that of ethanol as time progresses. By increasing PIto 50 MPa, the difference in DN(diffusion distance of the near side) between gasoline and ethanol is greatly reduced, meantime DF(diffusion distance of the far side) becomes weaker than ethanol. For both gasoline and ethanol, with the increase PIfrom 10 MPa to 50 MPa, VN(average normal component of droplet velocity) and VT(average tangential component of droplet velocity) of incident droplets increase by around 1 m/s. Meantime, there is a slight decrease in the absolute value of VNand VTof reflected droplets. DSMD(Sauter mean diameter of droplets) presents a significant decreasing trend with the increase of PI. Besides, a smaller DSMDcan be seen for the gasoline impingement spray compared to ethanol under the same PI.